Humoral immune response in multiple sclerosis patients following PfizerBNT162b2 COVID19 vaccination: Up to 6 months cross-sectional study - Achiron, Anat; Mandel, Mathilda; Dreyer-Alster, Sapir; Harari, Gil; Dolev, Mark; Menascu, Shay; Magalashvili, David; Flechter, Shlomo; Givon, Uri; Guber, Diana; Sonis, Polina; Zilkha-Falb, Rina; et al. (Journal of neuroimmunology, 2021)
Appropriate immune response following COVID-19 vaccination is important in the context of disease-modifying treatments (DMTs). In a prospective cross-sectional study, we determined SARS-COV-2 IgG response up to 6 months following PfizerBNT162b2 vaccination in 414 multiple sclerosis (MS) patients and 89 healthy subjects. Protective response was demonstrated in untreated MS patients (N = 76, 100%), treated with Cladribine (N = 48, 100%), Dimethyl fumarate (N = 35, 100%), Natalizumab (N = 32, 100%), and Teriflunomide (N = 39, 100%), similarly to healthy subjects (N = 89, 97.8%). Response was decreased in Fingolimod (N = 42, 9.5%), Ocrelizumab (N = 114, 22.8%) and Alemtuzumab (N = 22, 86.4%) treated patients. IgG response can help tailor adequate vaccine guidelines for MS patients under various DMTs. [Display omitted] •Immune responses after PfizerBioNTech COVID-19 vaccination differ in multiple sclerosis patients treated with various DMTs.•Durability of the anti-SARS-COV-2 IgG response to the vaccine was maintained up to 6 months post vaccination.•The relative impact of the time from the last dosing to vaccination is of significance to humoral IgG response.•Absence of SARS-COV-2 antibodies in patients treated with Fingolimod or Ocrelizumab suggests these patients will need a booster vaccine dose.